Pengaruh Penyuluhan terhadap Pengetahuan Ibu Hamil Trimester III tentang Nocturia di BPS Ny. Emy Desa Mangunrejo Kecamatan Ngadiluwih Kabupaten Kediri Tahun 2015 - Resmita Ardiansyah (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2016)
Pregnancy involves emotional and physical changes of the mother as well as the social changes in the family. At 28 weeks gestation, fetal head began to descend into the pelvis so that pressing the bladder and cause Frequent urination. The purpose of this study was to determine the effectiveness of counseling to the extension of the third trimester pregnant women knowledge about nocturia. The design of the study used a pre-experimental design approach One Group Pre-Post Test Design. The population was the entire third trimester pregnant women with the sample of 22 respondents taken by total sampling technique. The data collected by questionnaire and tested with paired sample t test. Respondents with a good knowledge criteria was 21 respondents (95.5%), respondents with sufficient knowledge criteria was 1 respondent (4.5%). Comparisons in this research was t <ttable (-9.1135 <- 2.080) with 23.0% of samples obtained difference with 38.4%. Counseling was important to increase knowledge of third trimester pregnant women about nocturia.